Lactylated acidic exopolysaccharide produced by the cyanobacterium Nostoc cf. linckia - Uhliariková, Iveta; Matulová, Mária; Košťálová, Zuzana; Lukavský, Jaromír; Capek, Peter (Carbohydrate polymers, 2022)
Cyanobacteria produce a wide range of metabolites of interest for industrial or medical use. The cultivation of freshwater Nostoc cf. linckia yielded 5.4 g/L of a crude exopolysaccharide (cEPS) with a molecular weight of 1.31 × 105 g/mol. Ion-exchange chromatography of cEPS yielded two dominant fractions, EPS-1 and EPS-2, differing in molecular weight. The lower molecular weight fraction (EPS-1) was subjected to structural studies. Results of chemical and spectroscopic analyses showed that three of the four dominant sugars, glucose, galactose and xylose are 1,4-linked in the backbone in the following order: [→4)-β-D-Xylp-(1 → 4)-β-D-Glcp-(1 → 4)-α-D-Galp-(1 → 4)-β-D-Glcp-(1→]n. Terminal mannose residues were identified as side chains linked at C3 of every third backbone xylose and every second glucose is branched at C6 by 3-O-lactyl-β-D-glucuronic acid (nosturonic acid). Antioxidant properties of EPS were tested using two in vitro methods. Both assays showed that the cEPS was more active than purified EPS-1 and EPS-2 fractions and deproteinized EPS.
Keywords: Polysaccharides, Bacterial; Antioxidants; Nostoc; kyselina glukuronová; Acidic exopolysaccharide; Molecular Structure; Xylose; Antioxidant activity; Nostoc cf. linckia; xylosa; magnetická rezonanční spektroskopie; molekulární struktura; molekulová hmotnost; bakteriální polysacharidy; glukosa; Glucose; galaktosa; antioxidancia; Galactose; Glucuronic Acid; Magnetic Resonance Spectroscopy; Molecular Weight; Structure; Nosturonic acid: 3-O-lactyl-β-D-glucuronic acid